Twenty-six years of the Indian "republic" : an assessment of the prospects for socio-economic transformation. - Indian Students Association:::Creator::::::::::::
Promotional poster for a discussion on prospects for meaningful socio-economic progress in India on January 24, 1976 and a photographic exhibition of images of social and political prospects in India, both sponsored by the Indian Students Association